Quenching characteristics of a continuously-heated rod in natural sea water. (April 2016) - Fu, Ben-Ran; Ho, Yuan-Hong; Ho, Ming-Xi; Pan, Chin
Highlights: The rod with continuously heating significantly increases the cooling time. The duration of film boiling can be shortened or even prevented in sea water. The Leidenfrost temperatures in sea water are higher than that in deionized water. The quenching performance and CHF are enhanced in sea water. Abstract: This study explores the quenching of a cylindrical rod with an internal heater in deionized water and natural sea water with pool temperature from 30 °C to 95 °C. An initial temperature of the testing rod ranges from 600 °C to 700 °C. Natural sea water may be used as emergency cooling water in a nuclear power plant near sea coast. The internal heater may be used to simulate the decay heat generated by the nuclear fuel rod after the power plant shutdown. The results demonstrate that film boiling occurs for the quenching in deionized water at any pool temperature investigated in the present study while it is absent when natural sea water is used with pool temperature below 70 °C. The maximal CHF of the non-continuously-heated case (or continuously-heated case) takes place in sea water at 30 °C, which reaches 2104 kW/m 2 (or 1936 kW/m 2 ), about 132% (or 136%) of that in deionized water. The Leidenfrost temperatures in sea water, if the film boiling is present, are considerably higher than that in deionized water resulting in much shorter quenching time in sea water than that in deionized water. The Leidenfrost temperature decreases as the pool temperature is increased, and the internal heat generation in the testing substance during the quenching process shows insignificant effect on it. In addition, the Leidenfrost temperature can be correlated as the function of the pool subcooling. In conclusion, this study demonstrates the enhancements of the quenching performance and CHF by using sea water as the coolant, instead of deionized water, which further indicates the beneficial sides of using natural sea water as emergency cooling water in a nuclear power plant.